PELATIHAN BAHASA INGGRIS LEVEL II BAGI PESERTA PROGRAM PENDIDIKAN KECAKAPAN KERJA (PKK) 2022 TAHAP II LKP ESSENTIAL ENGLISH CENTER BENGKULU - Eki Saputra; Fetriani Fetriani (Gapenas Publisher, 2023)
The number of stimulus numbers that hamper economic growth in the regions to the effect on the national. The Ministry of Education and Culture is promoting education and training programs specifically for people of productive age who are not yet working. Through cooperation with designated training and course institutions as partners in organizing activities. The Essential English Center is one of the institutions trusted as a partner of the Ministry of Education and Culture to organize a Work Skills Education Program (PKK) by providing skills, especially Level II English, to people of productive age and not yet working in Bengkulu without charging tuition fees from participants. With the implementation of the training program, it is hoped that the participants will gain knowledge and skills in English which will be useful for increasing their competitiveness in getting a job